PENGARUH SIKAP KEPADA INFLUENCER TERHADAP NIAT BELI KONSUMEN DI JAKARTA (STUDI PADA INFLUENCER BIDANG FASHION) - Yasir, Rania Ariqah; Said, Salsabila Rosalia; Kristaung, Robert (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
This research focuses on the involvement of fashion influencers in consumer purchasing intentions in Indonesia. This research uses a descriptive analysis research method with a quantitative approach. The sampling technique in this research uses the probability method combined with random sampling techniques. The sample used in processing the data was 116 respondents who were analyzed using the Structural Equation Modeling (SEM) analysis unit, which was run with the AMOS program and was then tested for the model’s goodness of fit to determine whether it was feasible. The conclusion obtained from this research is that there is a positive influence between Subjective Norms and Attitudes toward Influencers. This means that the increasing consumer perception of influencers can increase consumer attitudes towards influencers; There is a positive influence between perceived suitability and attitudes towards influencers. This shows that the more suitability felt by consumers towards the influencers they follow will increase consumers' attitudes towards influencers; Consumer attitudes towards influencers are positively related to consumer purchasing intentions, thus showing that using influencers they like will produce positive attitudes and therefore increase consumer purchasing intention.